Decision Support System for Determining Employee Bonuses using Analytical Hierarchy Process - Yuliyanti, Siti; Sartika, Tika (Department of Informatics, Siliwangi University, Indonesia, 2023)
Determining employee bonus salaries is one of the problems faced by every company, especially PT. Pyridam Farma, where the company finds it difficult to determine employees who are eligible to receive bonus salaries. There are many factors that cause this, including the fact that it takes quite a long time and the possibility of data being lost because it is still in hard copy form. This research uses the Analytical Hierarchy Process (AHP) as a weighting method for the basic criteria in determining employees who deserve a bonus salary, including length of service, absenteeism (attendance rate) and employee performance. The decision support system application determines employees who are eligible to receive this bonus salary on a web basis. The system that is built is able to determine which employees will receive bonus salaries based on predetermined weights and is able to determine what percentage of bonus salary employees will receive based on the assessments that have been carried out. This system can provide a solution for PT. Pyridam Farma to determine which employees will receive bonus salaries.